Defining the 'sick society': Discourses of class and morality in British right-wing newspapers during the 2011 England riots. (June 2015) - Kelsey, Darren
Between 6 and 10 August 2011, acts of violence and civil disobedience occurred in 66 locations across London and other cities in England. Initial responses from politicians and the press sought to explain why the riots were happening and what responses were necessary. This paper shows how the depoliticised actions of rioters were redefined as a politicised problem, symbolic of a sick society that could be cured by Conservative social policy. This paper explores the nuanced discursive and paradoxical mechanisms of right-wing newspapers. I argue that ideological consistencies operating beyond the foreground and immediacy of individual texts override the appearance of discursive contradiction across longitudinal contexts.